Identification, screening, and analysis of secondary metabolite content in methanol extracts of ant nests plant tubers from Aceh, Indonesia - ROSLIZAWATY ROSLIZAWATY; GHOLIB GHOLIB; NADIA RAHMI; KHAIRAN KHAIRAN; RINALDI IDROES; SYAFRUDDIN SYAFRUDDIN; MAHDI ABRAR (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Roslizawaty R, Gholib G, Rahmi N, Khairan K, Idroes R, Syafruddin S, Abrar M. 2023. Identification, screening, and analysis of secondary metabolite content in methanol extracts of ant nests plant tubers from Aceh, Indonesia. Biodiversitas 24: 6934-6941. This study aims to identify the chemical components obtained from extracting and partitioning methanol extracts from ant nest tubers (Myrmecodia sp.) originating from Aceh Jaya and Aceh Besar. These extracts were identified using phytochemical screening, Fourier Transform Infrared (FT-IR), and Gas Chromatography-Mass Spectroscopy (GC-MS) methods. The identification results showed that the ant nest plant from Aceh Jaya belongs to the species Myrmecodia tuberosa Jack. The ant nest plant from Aceh Besar belongs to the species Hydnophytum formicarum Jack. Phytochemical screening results showed that the methanol extract from Aceh Jaya's ant nest tubers contained flavonoids, tannins, saponins, and terpenoids, while Aceh Besar's ant nest tubers contained flavonoids, tannins, terpenoids. GC-MS analysis revealed that the major compound found in the methanol extract from Aceh Jaya's ant nest tubers was 2H-oxecin-2-one,3,4,7,8,9,10-hexahydro-4-hydroxy-10-methyl-,[4S-(4R*,5E,10S*)]- constituting 50.63% of the extract. In comparison, the primary compound in the methanol extract from Aceh Besar was resorcinol at 17.92%. FT-IR analysis indicated that the FT-IR spectra of the methanol extracts from Aceh Jaya's ant nest tubers contained O-H, C-H, C=O, C=C alkene, and C=C aromatic groups. At the same time, methanol extracts from Aceh Besar's ant nest tubers also contained O-H, C-H, C=O, C=C alkene, and C=C aromatic groups.